2009
DOI: 10.1186/1472-6963-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Perception of primary health professionals about Female Genital Mutilation: from healthcare to intercultural competence

Abstract: Background: The practice of Female Genital Mutilation (FGM), a deeply-rooted tradition in 28 countries in Sub-Saharan Africa, carries important negative consequences for the health and quality of life of women and children. Migratory movements have brought this harmful traditional practice to our medical offices, with the subsequent conflicts related to how to approach this healthcare problem, involving not only a purely healthcare-related event but also questions of an ethical, cultural identity and human rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 17 publications
6
53
0
Order By: Relevance
“…A response rate of around 75% has been estimated, similar to that obtained by the same system in a previous study by our group in 2001 and 2004 [14,15]. …”
Section: Methodssupporting
confidence: 87%
“…A response rate of around 75% has been estimated, similar to that obtained by the same system in a previous study by our group in 2001 and 2004 [14,15]. …”
Section: Methodssupporting
confidence: 87%
“…Eighteen percent of health professionals (including midwives) surveyed in Spain reported that they had no interest in learning about FGM. Less than half could correctly identify the different types despite approximately 30% of the population whom these professionals served, were immigrants from North African and nearly 14% from SubͲSaharan African countries where FGM is practiced (KaplanͲMarcusan et al, 2009). In Australia, a survey of health care practitioners revealed they had little knowledge or experience of the cultural and health issues relevant to FGM (Moeed & Grover, 2012).…”
Section: The Need For Professional Education and Supportive Environmementioning
confidence: 99%
“…Others postulated that FGC might be begun in societies where the women were subordinate to the men [4]. Regardless of its origin, FGC has been performed by Christians, Muslims, and Animists [5]. The practice was also common in United States of America and Europe in early 19th century where cutting of genitals was used to treat psychological disorders and prevent masturbation as well as “clitoral enlargement” [3].…”
Section: Introductionmentioning
confidence: 99%